Gelatinous zooplankton fauna (Cnidaria, Ctenophora and Thaliacea) from Baía da Babitonga (southern Brazil) - Júnior, Miodeli Nogueira (Zootaxa, 2012)
The present study reports on a survey of the gelatinous zooplankton fauna (Cnidaria, Ctenophora and Thaliacea) from theproposed Baía da Babitonga marine protected area (southern Brazil; ~26°S), based on collections from multiple sites overdifferent seasons and from published literature. In order to sample both small and large gelatinous animals, plankton hauls(n = 255) and fishing trawls (n = 126) were employed. More than 20,000 organisms were studied, which, includingliterature data, totaled 48 species: one cubomedusa, three scyphomedusae, four siphonophores, 36 hydromedusae, twoctenophores, and two thaliaceans. Among these, the hydromedusae Cnidostoma fallax Vanhöffen and Helgicirrha sp. arerecorded for the first time from the southwestern Atlantic coast and Paulinum sp. and Protiara sp. are recorded for thefirst time from the South Atlantic. A description of young stages of the hydromedusa Gossea brachymera Bigelow ispresented and shows that Octobulbacea montehermosensis Zamponi is a junior synonym of the former. Althoughcomprehensive local assessment of diverse taxonomic groups is still lacking, the high diversity observed herein underscores the importance of Baía da Babitonga as a high priority site for conservation of regional marine biodiversity.